2022
DOI: 10.9770/jesi.2022.10.1(8)
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social media marketing activities on green consumption intention: evidence from emerging countries

Abstract: The study investigated the impact of social media marketing activities on green consumption intention. The study used the survey method to describe this impact in five countries (Brazil, Egypt, India, South Africa, and Turkey). The analysis was applied to the leading platforms of electric car pages on social media -Facebook, TikTok, Twitter, YouTube, and Instagram. Five control variables (Age, Gender, Education, Income, and Citizenship) were used. A total of 393 questionnaires were collected in the first quart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
1
5
0
1
Order By: Relevance
“…Furthermore, green marketing strategies directly and substantially affect green credibility and image. The previous result is consistent with the results of Wagdi et al (2022) Based on the preceding discussion, the study found a research question as follows:…”
Section: Entrepreneurship and Sustainability Issuessupporting
confidence: 89%
“…Furthermore, green marketing strategies directly and substantially affect green credibility and image. The previous result is consistent with the results of Wagdi et al (2022) Based on the preceding discussion, the study found a research question as follows:…”
Section: Entrepreneurship and Sustainability Issuessupporting
confidence: 89%
“…The information bubble's role on social networks needs to receive more attention. Similar to the case of saving resources, the low relation of media exposure to waste management is rather surprising as previous research showed the opposite (Haron et al, 2005;Jain et al, 2020;Wagdi, et al, 2022) People living in large cities and in average-sized towns proved less prone to separate waste. Similarly to Xu et al (2017) and Challcharoenwattana and Pharino (2016), we suggest this reluctance to be related to the financial aspects of waste sorting.…”
Section: Waste Managementmentioning
confidence: 91%
“…This effect of online news might reflect the general polarization of ideas of environmental protection measures and the existence of climate change existing in online media (Pearce, 2019) or self-selection of the respondents. This result is rather surprising as much of research published in various times showed the media effect (Haron et al, 2005;Jain et al, 2020;Wagdi, et al, 2022).…”
Section: Saving Resourcesmentioning
confidence: 92%
See 1 more Smart Citation
“…All the perceptions, values and knowledge can be impacted by the mass-media and education. The impact of mass media on proenvironmental values and pro-environmental behavior was shown to be a significant one (Haron et al, 2005;Jain, et al, 2020;Wagdi, et al, 2022). Especially video content that is largely based on emotions has a particular influence on pro-environmental attitudes (Ramkissoon, and Smith, 2014).…”
Section: Green Purchasingmentioning
confidence: 99%